The operations of addition and scalar multiplication have been defined as: $$(a_1, a_2) + (b_1, b_2) = (a_1 + b_2, a_2b_2)$$ and $$k \cdot (a1, a2) = (k\,a1, a_2^k).$$

This was a problem on one of my tests, and I missed all possible points. When we went over the test, I paid attention to how it was supposed to be done, but did not write it on my test for reference. I tried looking for examples in my textbook, but there aren't any. Any help would be appreciated. My attempt:

zero vector: (a1, a2) + (0,0) = (a1 + 0, a2(0)) = (a1, 0) additive inverse: (a1, 0) + (0,0) = (a1, 0)

This is clearly wrong.

  • $\begingroup$ Welcome to MSE. please remember to use mathjax. Also it would be better if you write your try on every question :) $\endgroup$ – Arman Malekzadeh May 15 '16 at 15:22

For the zero vector: you can determine it from any of the two equations (which would make you check that they are compatible, which they are).

If $(a_1,a_2)+(z_1,z_2)=(a_1,a_2)$, this becomes $$(a_1+z_1,a_2z_2)=(a_1,a_2).$$ So you have $a_1+z_1=a_1$, $a_2z_2=a_2$. As you can do this for any choice of $a_1,a_2$, it follows that $(z_1,z_2)=(0,1)$.

Or, easier: $$(z_1,z_2)=0\cdot(1,1)=(0,1^0)-(0,1).$$

For additive inverse: if $(a_1,a_2)+(b_1,b_2)=(0,1)$, we have $$ (a_1+b_1,a_2b_2)=(0,1), $$ that is $a_1+b_1=0$, $a_2b_2=1$. So $b_1=-a_1$, $b_2=1/a_2$. So for $(a_1,a_2)$ with $a_2\ne0$, its additive inverse is $$\left(-a_1,\frac1{a_2}\right).$$

  • $\begingroup$ During my attempt today, I got it to (a 1 +z 1 ,a 2 z 2 )=(a 1 ,a 2 ). I knew that z 1 = 0, but for reasons unknown couldn't figure out that z 2 was 1. So in regards to the additive inverse, I only need to use the redefined addition and set it equal to the zero vector that was found, and then simplify. $\endgroup$ – Kevin May 15 '16 at 15:36

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.